Child brain exhibits a multi-rhythmic response to attachment cues. Issue 9 (22nd August 2018) - Pratt, Maayan; Goldstein, Abraham; Feldman, Ruth
Abstract: Research on the human parental brain implicated brain networks involved in simulation, mentalization and emotion processing and indicated that stimuli of own parent–child interaction elicit greater integration among networks supporting attachment. Here, we examined children's neural activation while viewing own parent–child interactions and asked whether similar networks activate when children are exposed to attachment stimuli. Sixty-five 11-year-old children underwent magnetoencephalography (MEG) while observing own vs unfamiliar mother-child interaction. Own mother–child interactions elicited a greater neural response across distributed brain areas including alpha suppression in posterior regions, theta enhancement in the fusiform gyrus and beta- and gamma-band oscillations across a wide cluster in the right temporal cortex, comprising the superior temporal sulcus/superior temporal gyrus and insula. Theta and gamma activations were associated with the degree of mother–child social synchrony in the home ecology. Findings from this exploratory study are the first to show activations in children that are similar to previous findings in parents and comparable associations between social synchrony and gamma oscillations in temporal regions. Results indicate that attachment stimuli elicit a strong neural response in children that spreads across a wide range of oscillations, underscoring the considerable neural resources allocated to this fundamental, survival-related cue.